Islamic Leadership in Developing the Character of Religious Moderation: Bibliometric Analysis - Muhammad Haris; Hidayatul Mufidah (Institut Attanwir Bojonegoro, 2024)
Administration in Islam plays a key part in forming devout control in different social orders. Devout control, which incorporates states of mind of resistance, regard for contrasts, and dismissal of radicalism, is vital for keeping up social agreement. In spite of the fact that this concept has long been recognized, investigate analyzing how Islamic authority contributes to cultivating devout balance through a bibliometric approach remains constrained. This ponder points to analyze the writing on Islamic administration and devout balance utilizing bibliometric strategies. The strategy utilized is bibliometric investigation bolstered by VOSviewer and Distribute or Die program. Investigate information were collected from the Scopus and Google Researcher databases over the past 10 a long time (2014-2024). This examination incorporates catchphrase arrange mapping, quotation examination, and connections among creators included in this subject. The comes about appear a noteworthy increment in distributions related to Islamic administration and devout control, with a add up to of 85 articles distributed within the final 10 a long time. VOSviewer investigation shows that 60% of the related articles look at the part of Islamic administration in instruction, whereas 25% center on its application in politics and society. The foremost habitually showing up watchwords are